Analysis of the Relationship between ALBI Score and APRI Score on Severity, Length of Treatment and Mortality in COVID-19 Patients at Dr. Saiful Anwar Hospital, Malang - Wibowo, Bogi; Mahendra, Aditya; Ibad, Ahmad; Santoso, Dimas; Eldatarina, Helsa (Universitas Brawijaya, 2024)
Background: Covid-19 is an infectious disease caused by the SARS-CoV-2 virus and has resulted in more than 3.8 million deaths worldwide. Covid-19 can cause multiorgan complications, including hepatobiliary organs. Many assessments have been used to determine the severity and prognosis of hepatobiliary disorders, such as the Albumin Bilirubin (ALBI) score and the AST-platelet ratio index (APRI) score. Aim: This study aims to determine the relationship between the ALBI score and APRI score with severity, length of treatment, and mortality in COVID-19 infection. Methods: We conducted a case-control study in a population of adult patients with confirmed COVID-19 who were hospitalized at RSSA in the period January-December 2022. Patients with hepatobiliary and autoimmune disorders were excluded from the sample population for further analysis. Albumin, bilirubin, SGOT, and platelet levels were measured at the beginning of the patient's hospitalization. The correlation between variables was analyzed using the Rank-Spearman test with SPSS 27. Results: The study subjects' characteristics showed that most patients were more than 60 years old (66.67%). Based on the severity of the disease, five patients (16.67%) were mild, ten patients (33.33%) were moderate, and 15 patients (50%) were severe. Of the 30 patients, 16 recovered (53.33%) and 14 died (46.67%). The majority of subjects did not require treatment in the ICU (66.67%). The results of the Rank-Spearman Test showed that the ALBI score [R=0.372; p=0.043 (p<0.05)] and APRI score [R=0.409; p=0.025 (p<0.05)] were significantly correlated with the mortality of Covid-19 patients but not with the severity and length of treatment. Conclusion: The conclusion of this study shows that ALBI score and APRI score have a significant relationship with mortality in COVID-19 patients and have the potential to be further studied as predictive factors in assessing the prognosis of COVID-19 patients.